Analisis penerimaan pengguna aplikasi e-Kinerja dengan metode TRAM dan EUCS pada kepolisian - Hadisuwarno, Anthony Eko; Bisma, Rahadian (Universitas Pesantren Tinggi Darul 'Ulum (Unipdu) Jombang, 2020)
This study aims to determine user acceptance and what factors influence user acceptance of E-Kinerja. The theoretical model used is a combination of the theoretical model of technology adoption of TRAM (Technology Readiness Acceptance Model) and EUCS (End User Computing Satisfaction). For example, the intention to use variable in the TRAM (Technology Readiness Acceptance Model) model is used as a link between the two models in this study. This research was conducted in Sidoarjo Police by using a questionnaire that was distributed directly as a source of data with probability sampling technique involving the participation of 229 respondents from Sidoarjo Police as members of the e-Kinerja application. The data analysis technique used is PLS-SEM (Partial Least Square-Structural Equation Modeling). The results of this study state that there are seven positive and ten negative hypotheses. The findings of this study are the user's intention to positively influence user satisfaction in using the e-Kinerja application which can be interpreted that the user feels satisfied and accepts the e-Kinerja application as an information system that can help reporting and calculating the performance of each member of the Sidoarjo Police.